RIGHTING OF CHINESE MITTEN CRABS (ERIOCHEIR SINENSIS) AND THEIR MODELS - Tobias Riphaus; Florian Hoffmann; Susanna Labisch (Acta Polytechnica CTU Proceedings, 2016)
The usage of unmanned underwater vehicles for marine tasks is continuously growing and bioinspired stabilizing systems shall help them to gain and keep a stable position during work. Therefore the righting maneuver of E. sinensis has been studied. These crabs are able to perform a 180°-rotation with an angular velocity of 4.30 s−1 when falling underwater from a supine starting position. High-speed particle image velocimetry has shown, that propulsive forces with a peak of 0.021 ± 0.001 N were produced by the hind legs to initiate and stop the rotation. In a numerical multibody simulation a constant force of 0.009 N acting for 0.2 s leads to the same rotation. In order to prove this mechanism, it was implemented into a robotic system. Its mean density of 1.15 g/cm3 deviates not more than 4% from the biological and numerical models. It can complete a 180°-turn within 1.03 ± 0.12 s with a rotational velocity of up to 4.25 s−1.